2005
DOI: 10.2320/matertrans.46.552
|View full text |Cite
|
Sign up to set email alerts
|

Trapping and Detrapping Mechanisms of Deuterium in SiC Studied by XPS and TDS Techniques

Abstract: The elucidation of the trapping and detrapping mechanisms of hydrogen isotopes in SiC is one of the most critical issues for future fusion reactors if SiC is used as the first wall and structure material. In this study, 1 keV deuterium (D 2 þ ) ions were implanted into SiC and the chemical states of C and Si were evaluated by X-ray photoelectron spectroscopy (XPS). The deuterium desorption and retention were also analyzed by thermal desorption spectroscopy (TDS). The deuterium desorption behavior for SiC was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…Comparison with the deuterium retention behavior in polycrystalline ␤-SiC reported in [5,7], two similar points were observed. For polycrystalline ␤-SiC, there are also two desorption peaks in TDS spectra and deuterium was also trapped preferentially by C in the initial implantation.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Comparison with the deuterium retention behavior in polycrystalline ␤-SiC reported in [5,7], two similar points were observed. For polycrystalline ␤-SiC, there are also two desorption peaks in TDS spectra and deuterium was also trapped preferentially by C in the initial implantation.…”
Section: Resultssupporting
confidence: 85%
“…It was reported that implanted hydrogen will be trapped by two vacancies in SiC, namely the carbon vacancy and silicon vacancy. If both types of vacancy are present, implanted hydrogen is preferentially trapped by silicon vacancy [7,8]. Therefore, for the trapping process of hydrogen isotopes, it was found that D was preferentially trapped by C in the initial D 2 + implantation.…”
Section: Methodsmentioning
confidence: 98%
“…6, in which the D retention in pyrolytic graphite (D/C) and SiC (D/ SiC · 0.5) are also shown [10,11]. The D retention in WC was decreased significantly up to 573 K, and the reduction became almost gradual above 573 K, where the amount of D bound to C was less than 20% of the D retention at 323 K. It should be noted that the D retention in WC was much less than those in the other materials, one fifth of that in pyrolytic graphite and one sixth in SiC.…”
Section: Resultsmentioning
confidence: 97%
“…Tritium transfer behavior through concrete material is studied at Kyushu University [38] and the diffusivity of water was expressed using the obtained adsorption isotherm. The hydrogen isotope behavior in typical plasma facing materials, namely graphite, SiC, WC and boron, were studied at Shizuoka University and The University of Tokyo, and the correlation between chemical state of materials and hydrogen isotope desorption process was discussed [39,40].…”
Section: Safetymentioning
confidence: 99%